VARIABEL-VARIABEL YANG MEMPENGARUHI VOLUME PENJUALAN PADA INDUSTRI KECIL KERAJINAN KULIT DI KOTA MADYA YOGYAKARTA - Wahyuningrum, Wahyuningrum (Jurnal Penelitian Humaniora, 2015)
Abstract The development of small and middle scale industries, including home industries, has been influencing the growth of the low and middle scale economics. The success of small scale and home industries were also influenced by the manager's skills in managing, arranging and making programs of future prospect and potentiality, but the small scale and home industries have to face a lot of problems to achieve the success. The study was aimed to know; how big the variables' influence on the sales volume of the small scale leather industry in the Yogyakarta municipality. The method used in this study was the quantitative method, of which the data were collected by questionnaire. The questionnaires were distributed to sixty-five respondents. The respondents were the manager marketing manager. Cluster random sampling was used. The statistical analysis used in this study was multiple regressions. The result of the multiple regression shows that these four independent variable were promotion, price, corporate culture and social had significantly influencing on the sale volume with an F of 152.17378 and p values of 0.000. the size of the influence of the four independent variables, simultaneously, on the sale volume could be obtained from the R2 value of 0.91027. Keyword: sale volume